Analisis Kesalahan Peserta Didik dalam Menyelesaikan Soal Teorema Pythagoras - Anwar Mutaqin; Cecep Anwar Hadi Firdos Santosa; Rohmatulloh Rohmatulloh (Universitas Sarjanawiyata Tamansiswa, 2022)
Most junior high school students have difficulty in solving math problems, causing students to make mistakes in solving math problems. The purpose of this study is to analyze the types of mistakes made by students in doing problems in the pythagorean theorem material. This type of research is qualitative descriptive research. The instruments in this study are test and interview instruments. The subjects of the study were as many as 9 students from class VIII at SMP Negeri 25 Kota Serang. The results of error analysis in this study show that students made mistakes in solving mathematical problems in the pythagorean theorem material in the form of fact errors, concept errors, principle errors and operating errors. The percentage of errors made by learners on factual errors was 17%, the percentage on conceptual errors was 44%, the percentage on principle errors was 17%, and the percentage on operating errors was 22%. The type of mistake most made by learners is the type of misconception. Concept errors occur because students do not understand the concept of pythagorean theorem material, causing students to have difficulty in solving mathematical problems in pythagorean theorem material.